2001
DOI: 10.1177/0261927x01020004001
|View full text |Cite
|
Sign up to set email alerts
|

Enacting Gender Identity in Written Discourse

Abstract: This study investigated ways in which gender identity is enacted within written language. Participants first supplied a self-descriptive letter that might be filed with a dating service. Next, they responded to a fabricated personal ad posted by a potential dating partner. Contextual factors in this study were writing task (self-description or response to a personal ad) and the gender role "bid" (either instrumental or expressive) of the hypothetical personal ad writer. Individual difference variables were bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Our findings are consistent with decades of research finding that women report using significantly more exclamation points than men, and men are more likely to report that they generally do not use exclamation points in their digital interactions (Scates, 1981;Rubin & Greene, 1992;Herring, 1994;Winn & Rubin, 2001;Colley & Todd, 2002;Waseleski, 2006). We also found that white women are more likely to use more exclamation points on the note of punctuation.…”
Section: Punctuation and Sexsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are consistent with decades of research finding that women report using significantly more exclamation points than men, and men are more likely to report that they generally do not use exclamation points in their digital interactions (Scates, 1981;Rubin & Greene, 1992;Herring, 1994;Winn & Rubin, 2001;Colley & Todd, 2002;Waseleski, 2006). We also found that white women are more likely to use more exclamation points on the note of punctuation.…”
Section: Punctuation and Sexsupporting
confidence: 89%
“…exclamation points (53%) than men (13.7%), and men are more likely to report not using exclamation points that much in general (47.1%) than women (14.9%). This is consistent with decades of research on gender differences in punctuation use (Carlos Scates, 1981;Colley & Todd, 2002;Diaz, 2018;Herring, 1994;Rubin & Greene, 1992;Waseleski, 2006;Winn & Rubin, 2001).…”
Section: Punctuation Usesupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, in a study conducted by Winn and Rubin (2001), it was found that writers changed their writing styles to complement (rather than converge toward) the apparent gender role orientation of their interlocutors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus, by increasing similarity through language, individuals can gain the approval of those they are interacting with. Divergence, or emphasis of a difference in style, can be used to signal distance or in interpersonal attraction contexts, signal gender characteristics of the two sexes (Winn & Rubin 2001). There is evidence that accommodation effects occur in friendly e‐mails to peers (Colley & Todd 2002; Colley et al .…”
Section: Introductionmentioning
confidence: 99%